Clinical audit of medical records based on clinical pathway: case study Benign Prostatic Hyperplasia (BPH) - Sugiarti, Ida; Setiadi, Dedi; Junaedi, Fadil Ahmad; Wahyuni, Ida (Poltekkes Kemenkes Bandung, 2026)
Background: Benign Prostatic Hyperplasia (BPH) is a common condition in adult men with a prevalence exceeding 50% by the age of ≥ 60 years. BPH causes symptoms of lower urinary tract infection, which reduces the quality of life and increases the burden of health services through visits, examinations, and medical interventions. BPH service practices still vary between health services, and medical records are still inconsistent and often deviate from clinical guidelines Objective: To examine the implementation of the BPH clinical pathway (CP) through clinical audit and explore its inhibiting factors. Methods: Qualitative research with a case study design in one regional referral service center. Data were collected through three triangulation sources: (1) observation of medical audits of 63 BPH patients' medical records, (2) in-depth interviews with 12 health workers (doctors and nurses), and (3) policy documents related to CP. Thematic analysis was carried out iteratively to identify patterns of CP non-conformity and implementation barriers. Results: Thirty-five percent of medical records did not meet CP criteria. Key obstacles included low awareness of the CP among healthcare workers, limited clinical time, and lack of integration of health information systems. Conclusion: The implementation of the BPH clinical pathway remains hindered by clinical and systemic factors. Evidence-based CP provides strategic solutions to improve service consistency and quality, but supporting policies, ongoing training, and integration of information systems are needed to optimize its application.